DOMESTIC VIOLENCE AGAINTS WOMEN IN THAILAND: GALTUNG-BASED ANALYSIS OF VIOLENCE IN THAI DRAMA “TIE ME (K)NOT” - Abimanyu, Akhdiat Dimas; Pulungsari, Rahadjeng (International Review of Humanities Studies, 2026)
This study examines the portrayal of domestic violence against women in the Thai drama Tie Me (K)not (2022) using Johan Galtung’s theory of violence, which categorizes violence into direct, structural, and cultural forms. Through qualitative content analysis, the research identifies how the drama depicts these forms of violence, reflecting broader societal issues in Thailand. The findings reveal explicit instances of direct violence, such as physical and psychological abuse, systemic structural violence through institutional failures in justice and support systems, and cultural violence rooted in patriarchal traditions that justify gender inequality. The drama not only highlights these oppressive dynamics but also challenges them through the protagonist’s journey toward empowerment. By analyzing these representations, the study underscores the role of media in raising awareness about domestic violence and advocates for societal and policy changes to address gender-based violence in Thailand. This research contributes to discussions on media, gender studies, and violence prevention, emphasizing the need for cultural and structural reforms to protect women’s rights.